1985
DOI: 10.1007/bf01959202
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil of Apium graveolens var. secalinum and its cercaricidal activity

Abstract: The composition of the essential oil of the fresh aerial parts of Apium graveolens var. secalinum at its flowering stage, obtained from three different locations in Egypt, was investigated. The identification of the components of this oil was carried out by means of analytical GC and GC-MS. The main components in the oil are: alpha- and beta-pinene, myrcene, limonene, cis-beta-ocimene, gamma-terpinene, cis-allo-ocimene, trans-farnesene, humulene, apiol, beta-selinene, senkyunolide and neocnidilide. Data concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
1
12
1
1
Order By: Relevance
“…The oil composition, in terms of the major constituents, does not seem to differ significantly from previously reported results [1][2][3][4][5] . Each of the essential oils has its own characteristic odour, which are due to the constituents they contained.…”
contrasting
confidence: 47%
See 2 more Smart Citations
“…The oil composition, in terms of the major constituents, does not seem to differ significantly from previously reported results [1][2][3][4][5] . Each of the essential oils has its own characteristic odour, which are due to the constituents they contained.…”
contrasting
confidence: 47%
“…rapaceum, had an abundance of monoterpene hydrocarbons such as α-and β-pinene and γterpinene 4,5 . Other varieties such as Apium graveolens var.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, Saleh et al (1985) identified a number of active compounds. 3-n-Butylphthalide was demonstrated to be a hypotensive as well as a hyocholesterolemic (Le & Elliott, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Egito perderam essa conotação espiritual e filosófica e os trabalhos egípcios atuais tendem a usar explicações científicas (ABDELGALEIL et al, 2008;ELSHAZLY;HAFEZ;WINK, 2004;SALEH et al, 1985;SAYED, 1980). …”
Section: Abordagem Filosóficaunclassified